PENJATUHAN PIDANA BERSYARAT TERHADAP KECELAKAAN LALU LINTAS YANG MENYEBABKAN KEMATIAN DITINJAU DARI UNDANG-UNDANG NOMOR 22 TAHUN 2009 - Raynold Rachwell (Fakultas Hukum Universitas Tarumanagara, 2020)
The purpose of Indonesian Penal punishment is deterrence. In order to pursue that purpose, criminal law introduce conditional sentences written in Article 14a of Indonesian Penal Code. The reason of conditional sentences being build is to prevent criminal course inside jail. Minor criminal that have been put in jail could be trading criminal skill with the other major criminal inside the jail, which could be cause of failure in the Penal punishment purpose. Conditional sentences could be apply to any kind of crimes according to Penal Code, therefore conditional sentences could be apply to traffic accident lead to dead cases. In this research, Writer found that some cases of traffic accident lead to dead have been applying conditional sentences, however exceed the limit of maximum sentences in Article 14a of Penal Code, hence causing inconsequent of written regulation and application. However, judge of the modern day should be able to anticipate difference of value in society and the regulation that is not up to date. So that the judges can returned the verdict in order to find justice according to value that live in society although the rule should be broken. Writer research this problem using normative researching method supported by interview data of expert and analysis of court verdict. So Writer expect there will be renewal in Indonesia Penal Code in order to keep the legal certainty.